Results of endovascular treatment of aortic valve disease in patients with intermediate surgical risk - I. Yu. Loginova; O. V. Kamenskaya; A. A. Prokhorikhin; A. R. Tarkova; E. I. Kretov; V. V. Lomivorotov; A. M. Karaskov (Российский кардиологический журнал, 2018)
Aim. To assess the results of a oneyear followup after transcatheter aortic valve implantation (TAVI) in patients with intermediate surgical risk with severe aortic stenosis.Material and methods. The study included 42 patients with hemodynamically significant aortic stenosis and intermediate surgical risk. We assess the incidence of prosthesisassociated complications, oneyear survival, clinical and hemodynamic characteristics, as well as the dynamics of the quality of life and social adaptation in the early postoperative period and one year after the intervention.Results. In patients with intermediate surgical risk prosthesisassociated complications were not registered in the early postoperative period and one year after TAVI, the survival rate was 97,6% and 88%, respectively. The hemodynamic effect of the operation according to the results of echocardiography persisted a year after the intervention with the positive dynamics of the myocardial contractile function. The quality of life a year after the TAVI increased on the scale of the physical health of the SF36 questionnaire from 25 (22;29) to 42 (28;46) points (p=0,031), on the mental health from 42 (33;50) up to 53 (48;57) points (p=0,025). The level of social adaptation has increased significantly; score of the Holmes and Rahe scale decreased from 250 (198;300) to 200 (180;220) (p=0,027). Conclusion. The hemodynamic efficacy of TAVI in patients with intermediate surgical risk with severe aortic stenosis is associated with a significant improvement of life quality and the level of social adaptation one year after the endovascular correction of valve defect.